2000
DOI: 10.1182/blood.v95.5.1680.005k33_1680_1686
|View full text |Cite
|
Sign up to set email alerts
|

The endothelial cell protein C receptor aids in host defense against Escherichia coli sepsis

Abstract: The influence of the endothelial protein C receptor (EPCR) on the host response to Escherichia coli was studied. Animals were treated with 4 separate protocols for survival studies and analysis of physiologic and biochemical parameters: (1) monoclonal antibody (mAb) that blocks protein C/activated protein C binding to EPCR plus sublethal numbers of E coli (SLEC) (n = 4); (2) mAb to EPCR that does not block binding plus SLEC (n = 3); (3) SLEC alone (n = 4); and (4) blocking mAB alone (n = 1). Those animals rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
119
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(127 citation statements)
references
References 40 publications
6
119
1
1
Order By: Relevance
“…They did, however, exhibit an eightfold increase in APC generation in response to infusion of thrombin and were partially resistant to a lethal dose of bacterial lipopolysaccharide. These findings confirm and extend the results of previous studies in which EPCR blocking antibodies were found to decrease protein C activation and increase susceptibility to bacterial sepsis in baboons [9,10]. Increased vulnerability to bacterial lipopolysaccharide also has been reported in EPCR-deficient mice [11], but until now no animal model was available to examine the consequences of EPCR overexpression.…”
supporting
confidence: 90%
“…They did, however, exhibit an eightfold increase in APC generation in response to infusion of thrombin and were partially resistant to a lethal dose of bacterial lipopolysaccharide. These findings confirm and extend the results of previous studies in which EPCR blocking antibodies were found to decrease protein C activation and increase susceptibility to bacterial sepsis in baboons [9,10]. Increased vulnerability to bacterial lipopolysaccharide also has been reported in EPCR-deficient mice [11], but until now no animal model was available to examine the consequences of EPCR overexpression.…”
supporting
confidence: 90%
“…As APC has been shown to increase survival in animal models of sepsis and EPCR has been implicated in the protection [6], we tested whether the Tie2-EPCR mice would be protected from the deleterious effects of LPS. The results clearly showed that the Tie2-EPCR mice were protected relative to wild type mice.…”
Section: Discussionmentioning
confidence: 99%
“…Activated protein C (APC) is a multifunctional plasma serine protease that exhibits anticoagulant, profibrinolytic, cytoprotective and anti-inflammatory activities [1][2][3][4][5][6][7][8][9]. Specific cofactors are required for the normal physiological function of APC in these diverse pathways.…”
Section: Introductionmentioning
confidence: 99%